Pentingnya Pemberian Asi Eksklusif Untuk Mencegah Stunting Pada Anak - Suradi Efendi; Nour Sriyanah; Andi Suci Cahyani; Sri Hikma; Kiswati K (PT.Mantaya Idea Batara, 2021)
Stunting is a linear growth disorder that is not appropriate for age. One of the factors causing stunting is not giving exclusive breastfeeding to infants (Sholihah, 2019) . Stunting prevalence A total of 151,398 children in South Sulawesi suffer from stunting or failure to thrive in 2020. They are spread over five districts with the highest stunting rates. Of the 24 regencies/cities in South Sulawesi, there are four regions with the highest stunting rates, namely in Bone Regency 43 percent, Enrekang 39 percent, Jeneponto 36 percent, Takalar 34 percent, and Bantaeng 33 percent (Head of the South Sulawesi Provincial Government Health Service). In the last year, there has been a reduction in the stunting rate of around 7000 cases. Meanwhile, last year, South Sulawesi was still in the top 10 with the highest stunting rate nationally. The goal is that participants are expected to be able to know about the importance of exclusive breastfeeding to prevent stunting in children. The method of community service is the planning, implementation, monitoring and evaluation stages. The target of the implementation of this service is 9 pregnant women. This implementation is assisted by various parties including the Head of Midwifery at the Paccing Health Center, Posyandu midwives and students to carry out community service. The results of community service found that pregnant women will apply it when the baby is born, starting from babies aged 0 to 6 months. The conclusion is that the community service carried out was successful in increasing exclusive breastfeeding to prevent stunting in children at the UPT Puskesmas Paccing Kab. Bone.